Pengaruh Media Pembelajaran terhadap Hasil Belajar Peserta Didik Kelas Sirkus di Red Nose Foundation Jakarta Utara - Shomalla Fadilah Anggraini; Muarifuddin Muarifuddin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The study evaluated the impact of learning media on student outcomes at Red Nose Foundation's circus classes in North Jakarta. It highlighted the importance of innovative and interactive media, especially in non-formal arts education, to improve understanding, skills, and motivation in mastering circus techniques. This research utilized a quantitative approach with simple regression analysis, selecting a purposive sample of 54 circus students from a total population of 119. Data was gathered using a closed questionnaire that had been validated and tested for reliability. The analysis indicated a significant positive impact of learning media on student learning outcomes. The coefficient of pearson corelation (R) was 0.974, indicating that 97,4% of the variance in student outcomes can be explained by the learning media used, with other factors influencing the remainder. In conclusion, learning media is crucial for enhancing learning outcomes in circus classes. Red Nose Foundation should continue developing relevant and tailored learning media that align with circus material and student needs. Additionally, instructors should receive training to use these media innovatively and effectively, ultimately improving learning efficiency and helping students achieve optimal results.